Pembelajaran kooperatif dengan pendekatan tutor sebaya untuk meningkatkan hasil belajar pada mata kuliah aljabar linear mahasiswa Informatika - Leni Reziyustikha (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
At mid-semester on the 2015-2016 academic year of Informatic Management program, the result shows that from 21 students there are 6 students got grade B where the rest are grade C, D, and E. Thus, a certain learning methodology is required to improve the quality of student’s grade namely cooperative learning peer-tutors method. The objectives are 1) to improve students learning output by cooperative learning as with peer-teaching method; 2) to observe students’ opinion regarding the learning process. The method is based on a case study with comparison of pre-test and post as a tool in a group. Based on research variable where cooperative learning with tutorage approach as an independent variable and learning quality output as a dependent variable. Population and sample in this research are determined by accessible considering time and research resource. The results are 1) there is improvement of student’s learning output with cooperative learning of tutorage approaching; 2) there is correlation between the cooperative learning with tutorage approaching student’s learning output at low, medium, and high level; 3) It improves students interest and ability to help students dealing with the subject.